Hesperidin alleviates hypothyroidism-related cardiac dysfunction by targeting cardiac miRNAs, Nrf2/NF-κB signaling, oxidative stress and inflammation - Gaber, Asmaa M.; Abdel-Moneim, Adel; Abdel-Reheim, Eman S.; Allam, Gamal; Abdul-Hamid, Manal; Hosni, Ahmed (Frontiers in Pharmacology, 2025)
BackgroundHypothyroidism is a frequent endocrine health issue that is linked to adverse cardiovascular events. Accumulating evidence suggests that thyroid hormone replacement does not fully reverse the cardiovascular complications associated with the disease despite normalization of serum thyroid hormone levels, indicating a need for adjunctive, complementary, or alternative therapies. Hesperidin (HSD) has diverse pharmacological activities, however, its therapeutic potential on the crosstalk between hypothyroidism and cardiac dysfunction has not been previously reported.MethodsThis study aimed to investigate the cardioprotective efficacy of HSD on carbimazole (CMZ)-induced hypothyroidism in rats in comparison to the traditional thyroid hormone replacement therapy; levothyroxine (LT4). Male Wistar albino rats were divided into four groups: normal control (NC), CMZ (30 mg/kg), CMZ + HSD (30 mg/kg CMZ + 200 mg/kg HSD), and CMZ + LT4 (30 mg/kg CMZ + 0.045 mg/kg). All doses were given orally and daily for 9 weeks.ResultsCMZ intake resulted in a significant decrease in thyroid hormones (THs) levels with a subsequent increase in serum thyroid stimulating hormone and cardiac enzymes activities, dyslipidemia, and body weight gain. Cardiac tissues revealed marked oxidative stress, inflammation, and structural degenerative lesions. As well, cardiac expression of miRNAs-92a and -499 was elevated while that of miRNA-21 was depleted, reflecting an interdependence between hypothyroidism and the development of cardiac dysfunction. Despite HSD and LT4 effectively alleviating the THs profile, only HSD offered substantial protection from hypothyroidism-associated cardiac inflammation and injury through its potent impact on the transcriptional miRNAs level and Nrf2/NF-κB protein expression (key regulators of the redox biomarkers and the inflammatory mediators).ConclusionHSD provides dual thyroprotective and cardioprotective effects that enhance THs bioavailability and functionality in the cardiovascular system.